OPTIMASI PENJADWALAN MATA KULIAH DENGAN ALGORITMA GENETIKA (Studi Kasus di AMIK JTC Semarang) - Entot Suhartono (Jurnal Ilmiah Infokam, 2015)
Course scheduling problems in a campus is a complicated thing. There are several methods for solving scheduling problems and produce an optimum schedule, such as genetic algorithms. In this research, problem solving course scheduling using genetic algorithms. This study aims to create genetic models for optimization scheduling optimization problem subjects. The case studies are taken in this study is the AMIK JTC Semarang with scheduling data on Odd Semester Academic Year 2014/2015. Then the schedule data is processed using a genetic algorithm optimization scheduling in order to obtain a condition where there is the best combination between subjects and leisure time of students, as well as the limited availability of space for all the existing courses. Based on trials that have been conducted, scheduling optimization model subjects with.   Key word : Scheduling Problem, Genetic Algorithm, Problem Solving, Optimization